2005
DOI: 10.1093/fampra/cmi076
|View full text |Cite
|
Sign up to set email alerts
|

Non-attendance in primary care: the views of patients and practices on its causes, impact and solutions

Abstract: Some non-attendance is inevitable with pre-booked appointments, as GP appointments must compete with patients' other priorities and the complexities of their day. Utilising modern communication technologies, such as SMS text messaging, may make cancellation simpler. A structured approach to matching supply and demand of appointments might reduce problems arising from non-attendance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 4 publications
2
104
0
7
Order By: Relevance
“…Entende-se que, mesmo tomando-se ações efetivas que reduzam significativamente o absenteísmo, este dificilmente será eliminado ou diminuído uma vez que parte das causas pode estar relacionada a fatores de difícil identificação, monitoramento e controle 28,29,30 . Assim sendo, medidas no sentido de minimizar os efeitos do absenteísmo, foco deste trabalho, são complementares e tão importantes quanto as iniciativas no sentido de reduzi-lo.…”
Section: Análise Dos Resultadosunclassified
See 1 more Smart Citation
“…Entende-se que, mesmo tomando-se ações efetivas que reduzam significativamente o absenteísmo, este dificilmente será eliminado ou diminuído uma vez que parte das causas pode estar relacionada a fatores de difícil identificação, monitoramento e controle 28,29,30 . Assim sendo, medidas no sentido de minimizar os efeitos do absenteísmo, foco deste trabalho, são complementares e tão importantes quanto as iniciativas no sentido de reduzi-lo.…”
Section: Análise Dos Resultadosunclassified
“…Considerando a dificuldade de identificar, monitorar e controlar os fatores que levam ao não comparecimento dos usuários no sistema público de saúde 28,29,30 , a adoção de uma técnica de maximizar o uso dos recursos públicos vai ao encontro dos anseios da sociedade 22,23,24 .…”
Section: Considerações Finaisunclassified
“…We developed an interview guide, based on factors and domains associated with patient-non-completion of health services identified from a review of the literature. [13][14][15][16]19,[31][32][33][34][35] Questions addressed the following topics: whether the patient had completed or missed any laboratory tests in the past year; underlying reason for laboratory tests; views on the importance of understanding the reason for the test; provider's explanation of the reason for the test; experience at lab; presence of reminder systems, from either the patient or the clinic; burden of and other barriers to laboratory testing; and speculation about reasons patients might miss tests. The initial interview guide was pilot tested with two patients for comprehension and flow, and was revised accordingly.…”
Section: Qualitative Methodsmentioning
confidence: 99%
“…Patients largely attributed non-completion to forgetting or a lack of awareness to the order instead of to the practicefactors, such as logistical access or laboratory facility hours, which previous studies have reported as important for patients missing clinician appointments. 15,16 Most patients did not advocate for a particular change within the clinical operations. Patient views and insufficient knowledge did not appear to lead to non-completion; most patients were able to explain, and believed it was important to understand, the reason for the lab test.…”
Section: Ged General Education Diplomamentioning
confidence: 99%
See 1 more Smart Citation